Peningkatan Motivasi Belajar Matematika Siswa Kelas IV Sekolah Dasar dengan Game Interaktif QuizWhizzer - Ardila Ardila; Pinkan Amita Tri Prasasti; Ritha Hima Watie (STIKes Ibnu Sina Ajibarang, 2024)
Learning mathematics is considered boring, challenging and only focuses on formulas and practice questions. The low motivation to learn from students in mathematics lessons is the basis for conducting this Kleas Action Research (PTK). The aim of this PTK is to use the interactive game QuizWhizzer to increase motivation to learn mathematics. From the research results of the implementation of the QuizWhizzer game, data was obtained that the pre-cycle stage got a percentage of 53.3% in the low category, in the first cycle stage it got a percentage of 69.5% which was categorized as medium, in the second cycle it got a percentage of 89.3% which was considered high. Thus, the QuizzWhizzer game can help students motivate themselves to learn mathematics.